2006
DOI: 10.1029/2004ja010793
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous resistivity and the nonlinear evolution of the ion‐acoustic instability

Abstract: [1] Collisionless magnetic reconnection requires the violation of ideal MHD by various kinetic-scale effects whose relative importance is uncertain. Recent research has highlighted the potential importance of wave-particle interactions by showing that Vlasov simulations of unstable ion-acoustic waves predict an anomalous resistivity that can be at least an order of magnitude higher than a popular analytical quasi-linear estimate. Here, we investigate the nonlinear evolution of the ion-acoustic instability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 29 publications
5
63
0
Order By: Relevance
“…In space science, 1D Vlasov simulation has been used to study the ion-acoustic instability of the initial drift Maxwellian or non-Maxwellian distribution in the magnetopause. It has been found that the anomalous resistivity in saturation state depends on reduced mass ratio, and increases with the enhancement of the mean drift velocity (Watt et al 2002;Petkaki et al 2003Petkaki et al , 2006. In 2D PIC simulations, Pritchett (2006) discovered that the most efficient electron acceleration in RCS takes place near the X-line of the externally driven RCS with a guiding magnetic field.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In space science, 1D Vlasov simulation has been used to study the ion-acoustic instability of the initial drift Maxwellian or non-Maxwellian distribution in the magnetopause. It has been found that the anomalous resistivity in saturation state depends on reduced mass ratio, and increases with the enhancement of the mean drift velocity (Watt et al 2002;Petkaki et al 2003Petkaki et al , 2006. In 2D PIC simulations, Pritchett (2006) discovered that the most efficient electron acceleration in RCS takes place near the X-line of the externally driven RCS with a guiding magnetic field.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The initial unstable waves originate in a white noise electric field applied at t = 0 (see Eqs. (4) and (5) in Petkaki et al 2003). The simulation parameters are summed in Table 1, where n, T are respectively the plasma density and temperature, v d , v e0 , and v i are respectively the initial bulk drift velocity, electron, and proton thermal velocity (…”
Section: Basic Equation and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the astrophysical and geophysical literature, the effect of the generation of anomalous resistivity in the regions with the high current density has been studied in great detail (see, e.g. Büchner & Elkina 2005;Petkaki et al 2006). We emphasise that the anomalous resistivity is generated before the fast wave pulse forms a shock, because the necessary condition for the onset of the current-driven instabilities is that the current density exceeds some certain (finite) threshold value (e.g., Yokoyama & Shibata 1994;Nakariakov et al 2006, for the discussion of this effect in the solar flare context).…”
Section: Parametric Studies 341 Compression Pulsementioning
confidence: 99%
“…This has its roots in the Boltzmann-Gibbs statistical mechanics, which is in turn based on the assumption that the collisions in the studied plasma are sufficiently frequent to attain the thermal equilibrium. However, the assumption of the Maxwellian distribution has been challenged in the past decades in a wide variety of astrophysical environments, ranging from laboratory plasmas to planetary magnetospheres, the solar wind, and even galaxies (e.g., Dalla & Ljepojevic 1997;Maksimovic et al 1997a,b;Viñas et al 2000;Petkaki et al 2003;Mauk et al 2004;Leubner 2004aLeubner ,b, 2005Maksimovic et al 2005;Ryu et al 2007Ryu et al , 2009Gaelzer et al 2008;Nieves-Chinchilla & Viñas 2008;Dialynas et al 2009;Prokhorov 2009;Prokhorov et al 2009;Le Chat et al 2009;Pierrard 2009;Pierrard & Lazar 2010;Livadiotis & McComas 2010;Lu et al 2010Lu et al , 2011Leitner et al 2011).…”
Section: Introductionmentioning
confidence: 99%